2009
DOI: 10.2139/ssrn.1514322
|View full text |Cite
|
Sign up to set email alerts
|

At Home and Abroad: An Empirical Analysis of Innovation and Diffusion in Energy-Efficient Technologies

Abstract: SummaryThis paper contributes to the induced innovation literature by extending the analysis of supply and demand determinants of innovation in energy-efficient technologies to account for international knowledge flows and spillovers. In the first part of the paper we select a sample of 38 innovating countries and we study how knowledge related to energy-efficient technologies flows across geographical and technological space. We demonstrate that higher geographical and technological distances are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…A set of recent empirical studies, assessing the technology transfers embedded in Clean Development Mechanism (CDM) projects, indicates that the second effect tends to be stronger, confirming the importance of capability in receiving countries (Dechezleprêtre et al 2008;Seres et al 2009). Verdolini and Galeotti (2009) also confirmed that knowledge increases the ability to benefit from disembodied international spillovers in the context of energy-efficient innovation. Keller (2004) reinforces this view in his survey of international knowledge spillovers by showing that an R&D effort is needed to absorb international knowledge.…”
Section: Determinants Of Climate-related Innovationsupporting
confidence: 53%
See 1 more Smart Citation
“…A set of recent empirical studies, assessing the technology transfers embedded in Clean Development Mechanism (CDM) projects, indicates that the second effect tends to be stronger, confirming the importance of capability in receiving countries (Dechezleprêtre et al 2008;Seres et al 2009). Verdolini and Galeotti (2009) also confirmed that knowledge increases the ability to benefit from disembodied international spillovers in the context of energy-efficient innovation. Keller (2004) reinforces this view in his survey of international knowledge spillovers by showing that an R&D effort is needed to absorb international knowledge.…”
Section: Determinants Of Climate-related Innovationsupporting
confidence: 53%
“…Peri (2005) studied the flow of knowledge across different countries in Europe and in North America, finding that aggregate innovation depends on internal and external knowledge. More recently, Verdolini and Galeotti (2009) used patent data for a group of OECD countries to study the determinants of innovation and the channels through which knowledge flows across countries. They suggested that more knowledge flows occur between innovator leaders and between similar countries.…”
Section: Determinants Of Climate-related Innovationmentioning
confidence: 99%